Occupancy history influences extinction risk of fossil marine microplankton groups - I. E. Smith; Á. T. Kocsis; W. Kiessling (Biogeosciences, 2025)
Geographic range has long been acknowledged as an important determinant of extinction risk. The trajectory of geographic range through time, however, has not received as much scientific attention. Here, we test the role of change in geographic range – assessed by a measure of proportional occupancy of grid cells – in determining the extinction risk in four major microplankton groups over the last 66×106 years: foraminifera, calcareous nannofossils, radiolarians, and diatoms. Logistic regression was used to assess the importance of standing occupancy and occupancy change in the extinction risk of species. We find that, while standing occupancy is a major determinant of extinction risk in all microplankton groups, the change in occupancy accounts for an average of 41 % of the explanatory power shared by the two analyzed variables, with a maximum value of 77 %. We also find that, as temporal resolution decreases, the predictive ability of these variables increases. Our results highlight the importance of incorporating both geographic range and its change through time into extinction models. The ability of occupancy trajectory to help predict extinction risk underlines the necessity of paleontological data in modern conservation efforts.